Genome-wide analysis of DNA methylation in testis of male rat exposed to chlorpyrifos. Issue 4 (4th August 2020) - Sai, Linlin; Jia, Qiang; Zhang, Yecui; Han, Ru; Geng, Xiao; Yu, Gongchang; Li, Shumin; Shao, Hua; Zheng, Yuxin; Peng, Cheng
Abstract: In our previous study, we found that subchronic exposure of chlorpyrifos (CPF) can cause reproductive damage in male rats. However, the mechanisms underlying the reproductive effects of CPF are not well understood. DNA methylation is essential for epigenetic gene regulation in development and disease. Therefore, we aim to compare DNA methylation profiles between controls and CPF-treated rats in order to identify the epigenetic mechanism of male reproductive toxicity induced by CPF. Methylated DNA immunoprecipitation with high-throughput sequencing (MeDIP-seq) was used to investigate the genome-wide DNA methylation pattern in testes of control and CPF-treated rats for 90 days. We identified 27 019 differentially methylated regions (DMRs) (14 150 upmethylated and 12 869 downmethylated) between CPF-exposed and control groups. The DMR-related genes are mainly involved in 113 pathways predicted by Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis. The result showed that high methylation gene PIK3CD may play a key role in epigenetic regulation of multiple pathways, such as Ras signaling pathway, AGE–RAGE signaling pathway in diabetic complications, HIF-1 signaling pathway, VEGF signaling pathway, and glioma and Fc epsilon RI signaling pathway in rats exposed to CPF. Our study provides significant explanations for the epigenetic mechanism of male reproductive toxicology induced by CPF.